Accessibility of Google Classroom by Undergraduates for Learning - Aderogba, Onojah Adenike; Shittu, Adedokun; Afolake, Nafisat; Ochayi, Onojah Amos; Musiliu, Aderoju Adekola (Universitas Pendidikan Indonesia (UPI), 2021)
Availability that lacks accessibility is nothing different from unavailability. The aftermath of COVID19 had forced most schools to employ several learning technologies with Google classroom inclusive. This study thus investigates undergraduate access to Google classroom for learning. This study employs the survey method and 250 undergraduates were purposively sampled. The findings established that undergraduate students have adequate access to google classroom for learning vocational and entrepreneurship courses and there was significant relationship between undergraduate access and utilization of google classroom for learning. The study concluded that access to Google classroom was directly proportional to its utilization. It was however recommended that lecturers should use the Google classroom to facilitate their instructional process.